Gas Flaring Effects and Revenue Made from Crude Oil in Nigeria - Yunusa, Nasiru; Idris, Ismail Tijjani; Zango, Adamu Garba; Kibiya, Muhammad Umar (International Journal of Energy Economics and Policy, 2016)
The study examines gas flaring and crude oil revenue in Nigeria. The study used secondary data for 14 years from 2000 to 2014 inclusive to analyze the issue using multiple regression analysis. The study employed time series data hence, a unit root test is conducted and found that they are stationary at level. Using three variables, gas flaring as the aggregate amount of gas flared by oil producing companies in Nigeria as an independent variable and crude oil revenue as an aggregate of revenue generated from all oil companies crude oil as dependent variable and tax as penalty on flaring is used as a control variable, the findings of the study show that gas flaring has a negative impact on Nigerian crude oil revenue and is statistically significant. From the research there are strong indications that the implementation of regulations and incentives to abate gas glaring in Nigeria has to be improving in other to increase revenue generated from crude oil. The author suggests that government should embark seriously on gas utilization policy and increase the penalty for companies who still engage in gas flaring. In addition, the government should utilize the gas flaring for electricity generation or implore another means of either utilizing it or curtail it. Keywords: Gas Flaring; Carbon Emission; Crude Oil Revenue JEL Classifications: Q51, Q53, Q56